(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
the cardiovascular and respiratory systems, on the one hand, allows to assess the level of adaptation of the athletes’ bodies to the conditions of sports activity and the adequacy of the proposed physical activity, which is very important for the health of those involved. On the other hand, knowing the individual characteristics of the athlete’s body’s adaptation to physical activity allows the coach and sports doctor to make adjustments to increase his effectiveness during training. Therefore, studies aimed at studying the characteristics of the functional state of the cardiorespiratory system in children who practice swimming are relevant.